CLASTERING CALON PENUMPANG KERETA CEPAT JAKARTA-BANDUNG - Muhammad Iqbal Firdaus; Reni Dian Octaviani; Indri Yusnita (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
This research aims to cluster prospective passenger high speed rail service corridor Jakarta-Bandung to compensate the rapid development Bandung City as one of the favorite tourist destinations for domestic and international visitors. The data analysis Method is using non-hierarchical cluster and sampling technique by random sampling with 280 respondents. The results show that there are three clusters of prospective passenger for high speed rail service with different characteristics. The first clusters are those who depend heavily on their private vehicles, the second cluster which is the largest cluster has logical ridership characteristics and the last cluster is a group that has a high level of concern for the environment.